PENGARUH KONSENTRASI EKSTRAK AKAR BAMBU TERHADAP PERTUMBUHAN DAN HASIL TANAMAN KACANG HIJAU PADA TANAH ALLUVIAL - varadibtya, friskananda dewi; astina, astina; arifin, nur (Jurnal Sains Mahasiswa Pertanian, 2019)
This study aimed to investigate the effect of bamboo root extract and find the best concentration on the growth and yield of mung bean on alluvial soil. This research was conducted in the village of Sungai Itik, Sungai Kakap District, Kuburaya. This study used a Completely Randomized Design (CRD), which consisted of a 6 treatments and 4 replication, each treatment consisting of 4 samples, so that there were 96 plants. The treatment were : p0 = without bamboo root extract, p1 = 10 ml/l, p2 = 20 ml/l, p3 = 30 ml/l, p4 = 40 ml/ l, p5 = 50 ml/l. The variables observed were to plant height, dry weight of plants, dry root weight, the number of productive branches, number of pods, weight of dry beans per plant, and weight of 100 dry seeds. The results showed that the bamboo root extract has a significant effect on plant height, dry weight of plants, the number of productive branches, weight of dry beans per plant, number of pods but bamboo root extract did not significantly affect the weight variable of 100 dry seeds. The best growth is achieved on administration 50 ml/l of bamboo extractKeywords: alluvial soil, bamboo root extract, mung bean